Intrathecal baclofen therapy for treatment of spasticity and dystonia in childhood - Ammar, Amr (2018)
Spasticity is a common presentation in a wide variety of neurological disorders like cerebral palsy (CP), multiple sclerosis, and spinal cord injury. Management of spasticity involves multiple modalities such as physical and occupational therapy, oral medicines, Botulinum toxin injection, and orthopaedic and neurosurgical intervention. Intrathecal Baclofen (ITB) therapy is one neurosurgical intervention to control spasticity in CP patients. The ITB pump is implanted subcutaneously or sub-facially in the abdomen which delivers the baclofen directly to the intrathecal space via a catheter. As a result of by-passing the blood-brain-barrier, intrathecal administration of a hundredth part of the oral baclofen dose is sufficient to relieve spasticity and therefore preventing the peripheral side-effects seen with oral administration. Although the ITB delivery systems demonstrate significant effectiveness in improving spasticity, the ITB delivery system is associated with a high complication rate which could interfere with the desired effect of ITB therapy. Therefore, in a retrospective observational study we aimed to analyse the ITB complications in a large (n=222) consecutive series of patients. The complication rate in relation to the long period of follow-up (939 pump years),was found to be similar or less than those reported in literature. Dystonia, young age and presence of gastrostomy tube were significantly associated with infective complications. Catheter complications were influenced by presence of dystonia and the surgical technique, whether it was a subfascial or subcutaneous implantation.